Genome-wide bioinformatics analysis of FMN, SAM-I, glmS, TPP, lysine, purine, cobalamin, and SAH riboswitches for their applications as allosteric antibacterial drug targets in human pathogenic bacteria. (3rd July 2019) - Pavlova, Nikolet; Penchovsky, Robert
ABSTRACT: Objectives : A constantly growing number of antibiotic-resistant strains of human pathogenic bacteria is an acute problem. Prolonged illnesses and increasing mortality worldwide mean that there is an urgent need to develop novel antibacterial drugs based on new targets and mechanisms of action. We present in silico analyses of bacterial riboswitches that may be suitable as antibacterial drug targets. Methods : Most bacterial riboswitches are allosteric cis-acting gene control elements located in the 5ʹ-untranslated region of messenger RNAs. Riboswitches sense specific metabolites and regulate the synthesis of some essential cellular metabolites in many pathogenic bacteria but are not found in humans. We present a complete and comprehensive genome-wide bioinformatics analyses of the suitability of eight riboswitches as antibacterial drug targets in various pathogenic bacteria. Results : Based on our in silico analyses, we classify the riboswitches in four different groups based on their suitability to be used as antibacterial drug targets. We have estimated that FMN, SAM-I, glmS, TPP, and Lysine riboswitches are promising targets for antibacterial drug discovery. Conclusion : This research enables us to focus antibacterial drug discovery research only on those riboswitches whose inhibition will result in suppression of the growth of certain pathogenic bacteria.